FEATURES OF AMBULATORY BLOOD PRESSURE MONITORING IN THE PERSONS WITH INITIAL STAGES OF THE CHRONIC CEREBRAL ISCHEMIA - Trishchynska М.А.; Halushko О.А.; Svystilnyk V.О. (World of Medicine and Biology, 2019)
Arterial hypertension is one of the major risk factors of cerebrovascular disease (CVD). The defeat of the cerebral vessels occurs within a certain time. The duration of this process depends on a number of blood pressure (BP) characteristics, which can’t be determined by conventional measurement of BP. For example, the important predictor of organ damage are blood pressure variability, the degree of night BP reduction, the blood pressure load. These rates are only available as a result of ambulatory blood pressure monitoring (ABPM). The purpose of our study was to investigate the characteristics of BP during 24-h and their prognostic value in patients with initial stages of the chronic cerebral ischemia. We examined 116 people with the initial manifestations of chronic cerebral ischemia. All patients underwent general-clinical, clinical neurology, clinical laboratory, neuroimaging examinations and ABPM. A difference was found between patients in groups 1 and 2 (A and B) according to the daily index (DI) of systolic and diastolic blood pressure - in persons with structural changes at MRI was insufficient reduction of blood pressure at night. In 58,9% of the patients who were examined, the rate of systolic blood pressure rising in the morning was increased, the magnitude of the morning rise of systolic blood pressure exceeded 55 mm Hg. in 18.1% persons, the magnitude of the morning rise of the diastolic blood pressure exceeded 35 mm Hg. in 34.3%. The level of glucose had a reversible moderate relationship with the level of systolic and mean blood pressure. The level of the C-reactive protein (C-RP) significantly correlated with the pressure load of systolic blood pressure in the day (r = 0.497, p = 0.042). As the load of systolic blood pressure increases, there was a tendency to increase the level of nonspecific inflammatory markers, which include fibrinogen and C-RP. The presence of small vascular lesions in the white matter of the brain associated with the non-dipper type (Х2(1) = 5,22; p=0,02).With the level of systolic blood pressure load at night was associated the presence of small vascular lesions (Х2(1) = 6,1; p=0,014) as well as with presence of cerebral atrophy (Х2(1) = 5,4; p=0,02). The obtained data permit to make the following conclusions. Patients with different degree of cerebral damage did not differ statistically by the average daily ABPM indices, by the magnitude of the morning elevation of blood pressure (both systolic and diastolic), by the rate of morning rise of systolic blood pressure and the prevalence of certain daily blood curves. In individuals with structural changes in the brain according MRI, there was an insufficient reduction in blood pressure at night compared with patients in group 1. In the majority (58.9%) of patients the rate of rising of systolic blood pressure in the morning was increased, which indicated a possibility of negative influence on the vascular system in the absence of obvious signs of the burden of blood pressure even at the background of antihypertensive therapy in patients with initial manifestations of chronic cerebral ischemia. Increased load by systolic blood pressure at night significantly affected the risk of structural damage of the brain.